Localization of a Sound Source in Double MS Recordings - KLECZKOWSKI, Piotr; PLEWA, Magdalena; PYDA, Grzegorz (Archives of Acoustics, 2008)
In recent years new solutions and systems emerge to be used in spatial recording and sound reproduction. The aim of this paper is to investigate and describe sound localization in a horizontal plane in Double MS recordings. Double MS is a spatial microphone technique, which evolved from the intensity MS stereo system. There are many possibilities to decode recorded signals to different audio systems including the Surround 5.1 system. Localization of a sound source in the horizontal plane, which is the most important issue in surround audio systems, is a complicated phenomenon. It is not possible to describe it by using only mathematical models, so we performed a subjective listening test to obtain some quantitative data. The results of the test and the advantages of the MSM technique lead to the conclusion that this microphone system can be used successfully in spatial sound productions.